Natriuretic peptides in heart valve disease. Issue 9 (26th October 2005) - Ray, S G
Abstract : Synthesis and release of B-type natriuretic peptide (BNP) are increased in heart failure, and plasma concentrations provide important therapeutic and prognostic information. Recent studies have shown that BNP concentrations are also increased with disease of the mitral and aortic valves. The extent of the increase is broadly related to the severity of the valve abnormality and the degree of consequent cardiac remodelling. BNP concentrations appear to relate to prognosis in these patients and might have a role in identifying suitable candidates for cardiac surgery. This paper reviews the current literature and identifies areas where further research is required if assessment of BNP is to be of practical use.